(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
Depending on fossil fuels such as crude oil is becoming a big environmental and economic dilemma. Fossil fuels release carbon oxides which hurt the environment by forming greenhouse effect which leads to the global warming and climate change. Moreover, countries over the world and especially Iraq use the crude oil and natural gas daily which makes this fuel expensive and threatened to be stopped one day. In this study, a simple review focuses on renewable energy as a clean and cheap energy that they could be recommended to use safely in Iraq. In conclusion, the renewable energies are the optimal solution to avoid the increased cost of the crude oil and reducing the risk of the environment pollution.